2004
DOI: 10.1021/ja0485513
|View full text |Cite
|
Sign up to set email alerts
|

New Beginnings for Matrix Metalloproteinase Inhibitors:  Identification of High-Affinity Zinc-Binding Groups

Abstract: In an effort to identify promising non-hydroxamate inhibitors of matrix metalloproteinases (MMPs), several new zinc-binding groups (ZBGs) based on pyrone, pyrothione, hydroxypyridinone, and hydroxypyridinethione chelators have been examined. Structural studies with tris(pyrazolyl)borate model complexes show that these ligands bind to the MMP active site zinc(II) ion in a bidentate fashion, similar to that found with hydroxamate-based inhibitors. Fluorescence- and colorimetric-based enzyme assays have been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
189
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(196 citation statements)
references
References 16 publications
7
189
0
Order By: Relevance
“…This may be related to the lack of selectivity of hydroxamic acid for zinc over other divalent transition metals, including the ability to bind metal ions in several oxidation states such as iron (III). In addition, the hydroxamate carbon-nitrogen bond (C[ ¼ O]NHOH) can easily change to the trans configuration reducing its affinity (Puerta et al, 2004).…”
Section: Zinc-binding Groupsmentioning
confidence: 99%
“…This may be related to the lack of selectivity of hydroxamic acid for zinc over other divalent transition metals, including the ability to bind metal ions in several oxidation states such as iron (III). In addition, the hydroxamate carbon-nitrogen bond (C[ ¼ O]NHOH) can easily change to the trans configuration reducing its affinity (Puerta et al, 2004).…”
Section: Zinc-binding Groupsmentioning
confidence: 99%
“…Towards our goal to achieve selectivity we utilized the acquired scientific experience from the matrix metalloproteinases (MMPs) family of zinc endopeptidases, which has been intensively pursued during the last three decades. [18][19][20] Specifically, it has been demonstrated that employing strong zinc chelators, [21][22][23] 0960-894X/$ -see front matter Ó …”
mentioning
confidence: 99%
“…In particular, the catechol moiety of compound 6 appears to be the key functional region of the molecule as it chelates the Zn 2+ ion while aliphatic the five member ring fits nicely into an adjacent hydrophobic pocket (Figures 2A, C). The catechol functionality has been shown previously to be involved in the inhibition of various other metallo-proteases [18][19][20][21]. Interestingly, the hydroxyls groups are also predicted to be simultaneously involved in hydrogen bond interactions with the carboxylates of Glu 687 and Glu 375, side chains coordinating the metal ion (Figures 2A, C).…”
Section: Resultsmentioning
confidence: 82%